Non-linear dynamics and statistical theories for basic geophysical flows - Majda, Andrew, 1949- (Cambridge University Press, 2006)
Geophysical fluid dynamics illustrates the rich interplay between mathematical analysis, nonlinear dynamics, statistical theories, qualitative models and numerical simulations. This self-contained introduction will suit a multi-disciplinary audience ranging from beginning graduate students to senior researchers. It is the first book following this approach and contains many recent ideas and results.